All-cause mortality and its risk factors among type 1 and type 2 diabetes mellitus in a country facing diabetes epidemic. (August 2016) - Al-Rubeaan, Khalid; Youssef, Amira M.; Ibrahim, Heba M.; Al-Sharqawi, Ahmad H.; AlQumaidi, Hamid; AlNaqeb, Dhekra; Aburisheh, Khaled H.
Highlights: This is the first study assessing diabetes all-cause mortality in the Middle East. The high diabetes prevalence is associated with greater absolute number of deaths. Secondary prevention programs for diabetes complications should be initiated. Establishing a proper diabetes cause-specific death registry is highly recommended. Diabetes excess mortality at young age should be addressed in prevention programs. Abstract: Aim: Diabetes mellitus is associated with an increased risk of premature death mainly secondary to macrovascular and microvascular complications. Mortality data from the Eastern Mediterranean region known for its high diabetes prevalence are lacking. We aimed to assess all-cause mortality and its predictors using large cohort from the Saudi National Diabetes Registry (SNDR). Methods: The study population comprised of 40, 827 individuals with type 1 and type 2 diabetes mellitus aged ⩾25 years registered in SNDR between January 2007 and December 2013. All patients were followed until death, according to the date of death or reaching 100 years of age or end of the study. Death was verified from the national civil affairs database. The general population during the study period was used as a reference for standardized mortality ratio (SMR) calculation. Results: With a total of 152, 038 person-years of follow up, 2582 patients were deceased giving all-cause mortality rate of 16.98 per 1000 person-years and SMR (95% CI) of 1.93 (1.86–2.00). Mortality rates were higher among men and increased with age, while SMR attenuated with increasing age. The independent predictors for all-cause mortality were longer diabetes duration, presence of macrovascular complications, nephropathy, retinopathy, hypertension, male gender and older age, while morbid obesity and the presence of hyperlipidemia were associated with reduced risk. Conclusions: The unexpectedly low mortality rate in this population would be associated with higher number of deaths as a result of the high prevalence of diabetes and its complications. Reducing the prevalence of diabetes and its complications would reduce the risk of mortality.